Association between Illness Perception and Anxiety Undergoing Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome: A Pilot Study - Achmad, Bayu Fandhi; Setiyarini, Sri; Sutono, Sutono; Rasyid, Frida; Fitriawan, Akbar Satria; Kafil, Raisa Farida (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Patients’ illness perceptions are thought to be associated with anxiety undergoing percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS). AIM: This study aimed to determine the association between illness perception and anxiety undergoing PCI in patients with ACS. METHODS: This study used a cross-sectional design and enrolled 50 hospitalized patients with ACS who underwent elective PCI between December 2019 and March 2020. The study instruments were the Brief-Illness Perception Questionnaire to evaluate illness perception and the Zung Self-Rating Anxiety Scale to evaluate patients’ anxiety. Statistical analysis was performed using the Pearson correlation test with significance set as p < 0.05. RESULTS: This study showed that 56% of respondents had positive perceptions toward their disease. The majority of respondents (94%) also indicated a low level of anxiety undergoing PCI. The Pearson correlation test results revealed a significant association between illness perception and the level of anxiety undergoing PCI in patients with ACS (p = 0.043; r = 0.287). CONCLUSION: There is a significant association between illness perception and anxiety undergoing PCI in patients with ACS. The positive perceptions led to lower patients’ anxiety, and vice versa.